Cover Feature: Rational Design of a Composite Electrode to Realize a High‐Performance All‐Solid‐State Battery (ChemSusChem 12/2019). Issue 12 (24th June 2019) - Kim, KyungSu; Park, Jesik; Jeong, Goojin; Yu, Ji‐Sang; Kim, Yong‐Chan; Park, Min‐Sik; Cho, Woosuk; Kanno, Ryoji
Abstract : The Front Cover shows the robust design of a composite electrode in which an ionic liquid is utilized as a pore filler, thereby, enabling a high‐performance all‐solid‐state battery. Using ionic liquid as a pore‐filler improves the contact area between the cathode materials and the solid‐electrolyte particles and minimizes overpotential at the interfaces. Based on a conventional electrode fabrication process, the proposed all‐solid‐state battery exhibits comparable electrochemical performance to conventional lithium‐ion batteries at room temperature. This can provide a practical guideline for developing high‐performance all‐solid‐state batteries. More information can be found in the Full Paper by Kim et al. on page 2637 in Issue 12, 2019 (DOI: 10.1002/cssc.201900010 ).